Estrategias didácticas para el proceso de enseñanza aprendizaje de Matemáticas en bachillerato - Cartuche Sanmartin, Odalis Briggette (2024)
The application of didactic strategies in the classroom strengthens students' critical, socio-emotional and creative skills, facilitating quality education. The general objective of the research was to determine the didactic strategies that favor the teaching-learning process of Mathematics in baccalaureate. It was framed in a mixed approach, its scope was descriptive with a non-experimental design. For its organization, the deductive, inductive, documentary and statistical review methods were used. In addition, the collection of information was obtained through the implementation of the techniques of collection and observation, being the bibliographic records and checklist their instruments, respectively. The most outstanding results indicate that didactic strategies such as master class, exercises and individual workshops are frequently applied in the classroom, and the student is a passive being in his or her learning. In conclusion, pedagogues apply traditional and non-innovative didactic strategies, generating monotonous educational environments and disinterest in the subject. Keywords: Didactic strategies, teaching-learning process, didactic sequence, microcurricular planning, mathematical skills.